Estudio de mercado emisor en el consumo de turismo arqueológico en Manabí - Intriago Cedeño, Vanessa Elizabeth (2019)
The current work was to carry out a study of the issuing market in order to establish contributions that increase the consumption of archaeological tourism in Manabí. The research was of a mixed nature with a descriptive approach structured in three phases that respond to the proposed objectives, beginning with the valorization of archaeological resources as the first phase where it was determined that Manabí is a destination with potential for the development of this, however the ignorance of the market that practices this modality and others have generated insipience in its consumption, later the main resources (museums and archaeological sites in Manta, Montecristi, Puerto López and Portoviejo) were registered and based on it the valuation through a matrix resulting as a resource with greater potential the commune Agua Blanca. Consequently, in the second stage a demand study was carried out determining that the visitor is characterized by being Ecuadorian, traveling in a group of university friends between 25 and 48 years who spend the night for 3 to 6 days and perceive the destination as good; The offer is determined to be limited and meets the necessary conditions, but is deficient. Finally, in the third phase that corresponded to propose marketing strategies, actions were established in accordance with the 4Cs that consist of preparing an offer according to the market in reference to the consumer, convenience and communication, allowing to structure an archaeological product proposal reflected in a route that integrates visit to museums and potential sites that allow the attraction of visitors.